Fibromyalgia as an interdisciplinary problem — the possibilities and prospects of diagnosis and treatment - O. V. Kolokolov; E. A. Salina; T. O. Kolokolova; E. V. Lukina; I. V. Sitkali (Лечащий Врач, 2021)
The article discusses fibromyalgia (FM) as a topical interdisciplinary problem. From the point of view of modern medicine, FM is considered a chronic disease characterized by widespread persistent musculoskeletal pain of a non-inflammatory nature, which is accompanied by fatigue, sleep disturbances and cognitive impairments. The authors focused on a review of the literature on the etiology of FM, which is a multifactorial disease — in particular, genetic predisposition and the state of the intestinal microbiota are of great importance in its development. The criteria for clinical diagnosis of FM should be widely used — the diagnosis can be made in primary health care settings based on the assessment of compliance with the criteria of The American College of Rheumatology (ACR, 2016) and subject to normal results of physical examination and laboratory tests, excluding other diseases. The authors draw attention to the importance of an integrated approach (pharmacotherapy, physical rehabilitation, psychotherapy) in the treatment of FM — the point of view of doctors and psychologists is presented.